User-friendly Web application for bibliographic material processing. - Belic K; Surla D (Electronic Library, 2008)
Purpose-The purpose of this paper is implementation of a software system for bibliographic material processing which does not require knowledge about any format for bibliographic data input. This means that the input can be done not only by librarians, but also by other persons such as authors of bibliographic units, students, employees, etc.Design/methodology/approach-An object-oriented methodology for developing information systems by means of computer-aided software engineering (CASE) tools and software components is used. The software architecture is multi-layered and web-based. The implementation is done in Java environment.Findings-The result is a web application by which users can catalogue bibliographic material without being familiar with the corresponding format. Nevertheless, the bibliographic record is formed in accordance with the given format for bibliographic material processing (MARC21, UNIMARC, etc.).Research limitations/implications-Automatic generating of screen forms for the chosen set of data for bibliographic material processing is not provided in the presented version of the application. In order to eliminate this limitation, there are preset solutions that can be integrated into the application.Practical implications-The application is primarily intended for research institutions aiming at forming their electronic catalogue and/or bibliographies of researchers or institutions.Originality/value-The originality of the paper lies in the software architecture of the application related to the middle layer, i.e. the one of business logic. This layer implements a mechanism by which different sets of input data are mapped to persistent data by means of the unique object model of an accepted format for the bibliographic material processing (MARC21, UNIMARC, or others).